MANOHAR MALGONKAR - “THE INDIAN KIPLING” - Jadhav, Swapna (International Journal of Research -GRANTHAALAYAH, 2016)
Manohar Malgonkar a versatile Indian fictional writer represents the life of pre independent and of post independent India that has left heavy memories of events which changed our nation’s history and society in the most profound ways. His novels “ Distant Drum” (1960), “Combat of Shadows “(1962),” The Princes” (1963), “A Bend in the Ganges” (1964), and “The Devil’s Wind” (1972) witness a wonderful knock of weaving plots of singular originality. His themes such as the army life, the aristocracy, commonality, partition of India, violence, sex, hunting, betrayal and revenge actually provides scope to find out the depth of Human relationships.“There is no exaggeration in calling him “INDIAN KIPLING”. Malgonkar has similarities with R.K. Narayan. Both are contemporary Indian fiction writers in English and have experimented with the English language. He finds India under the pressures of modern education and industrialization changing its virtues and reminds us to overcome the evil factors. As a contemporary of writers such as Mulk Raj Anand and Khushwant Singh, it is a fact that Malgonkar’s contribution to the genre we refer to today as Indian Writing in English remains largely unacknowledged.